Lietuvių ir anglų kalbų giminės kategorija ir jos stilistinis vartojimas - Bražėnienė, N. (Kalbotyra, 1979)
This paper presents analysis of the category of gender in Lithuanian and English. Stylistic confrontation of the category of gender in Lithuanian and English is possible only on semantic basis. Apart from its denotative meaning the grammatical category of gender may have various connotative functions in both languages. The most expressive use of the category of gender is found in personification.